2021
DOI: 10.1136/tobaccocontrol-2020-056310
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco mythbusting—tobacco is not a major driver of foot traffic in low socio-economic small retail stores

Abstract: BackgroundOne of the opposing arguments to restricting or banning the sale of tobacco products stem from a perception that this would adversely impact on small retail stores that rely on tobacco sales for viability. It has also been argued that purchases of tobacco leads to unplanned purchasing of other items that yield income for small store owners. This study tested the veracity of these arguments in the Australian context.MethodsConsumer intercept surveys (n=1487) were conducted outside a comprehensive samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…[105][106][107] Indeed, studies from Australia, New Zealand and the USA found that sales transactions with tobacco products represented a smaller fraction than industry estimates, and tobacco manufacturers and retailer associations overstate retail profits from tobacco. [108][109][110][111][112] Further evidence to refute industry claims may encourage retailers to abandon tobacco and transition to more profitable product lines, 113 reducing both the oversupply and visibility of tobacco products. Additionally, policies that prohibit tobacco industry contracts and incentives to promote and sell tobacco products in the retail setting are needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[105][106][107] Indeed, studies from Australia, New Zealand and the USA found that sales transactions with tobacco products represented a smaller fraction than industry estimates, and tobacco manufacturers and retailer associations overstate retail profits from tobacco. [108][109][110][111][112] Further evidence to refute industry claims may encourage retailers to abandon tobacco and transition to more profitable product lines, 113 reducing both the oversupply and visibility of tobacco products. Additionally, policies that prohibit tobacco industry contracts and incentives to promote and sell tobacco products in the retail setting are needed.…”
Section: Discussionmentioning
confidence: 99%
“…More evidence is needed to refute tobacco industry opposition to retail regulation,103 104 including studies that both debunk industry ‘footfall’ claims about tobacco driving customers to stores and highlight success of retailers who abandon tobacco sales 105–107. Indeed, studies from Australia, New Zealand and the USA found that sales transactions with tobacco products represented a smaller fraction than industry estimates, and tobacco manufacturers and retailer associations overstate retail profits from tobacco 108–112. Further evidence to refute industry claims may encourage retailers to abandon tobacco and transition to more profitable product lines,113 reducing both the oversupply and visibility of tobacco products.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of tobacco footfall is also likely to differ between retailer types. 14 These retail data do not include information about customers and so could not capture shoppers' characteristics, motivations for visiting stores or frequency of purchasing. In the analysis, baskets containing tobacco were presented as an indicator of tobacco's role as a footfall driver and non-tobacco products purchased alongside tobacco were presumed to be 'secondary purchases'.…”
Section: Methodological Strengths and Limitationsmentioning
confidence: 99%
“…7 14 Consumer intercept surveys of shoppers exiting stores in case study areas in the USA, New Zealand and Australia have found that just 8%-14% of transactions contained tobacco. [14][15][16][17] Additionally, tobacco shoppers did not necessarily make significant 'secondary purchases' as 60%-64% of these shoppers bought tobacco alone. [15][16][17] A 2015 analysis of point of sale data in the UK indicated that tobacco was purchased by a minority of shoppers, was often purchased alone and the value of any nontobacco copurchases was similar to that purchased by shoppers who did not buy tobacco.…”
Section: Original Researchmentioning
confidence: 99%
See 1 more Smart Citation